2021
DOI: 10.31328/jsed.v4i1.2274
|View full text |Cite
|
Sign up to set email alerts
|

Higher education leadership and uncertainty during the COVID-19 pandemic

Abstract: The impact of the pandemic on higher education activities is a major concern around the world. Higher education is obliged to carry out the necessary measures of adaptation, innovation, and management change, which are promoted by leaders at various levels. The leadership is further committed to encouraging transformative changes to meet students’ most critical needs.  Leadership is expected to be able to use all resources in the organization, even in limited conditions due to pandemic impacts.  The crisis con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
10
0
3
Order By: Relevance
“…Innovative leadership in education can be realized in managing and making decisions for the evaluation phase, starting at the planning, management, indicator development stages into a core program of innovative leadership in learning by paying attention to the adaptation of responsive and applicable information technology for implementation (Syafaruddin, Asrul, Mesiono, 2019). This is in line with the research of Nugroho et al, (2021) which says that innovative leadership is suitable in dealing with crises because of the advantages it has, such as 1) being able to anticipate needs, modes of interest and choice in the future, 2) being active in building knowledge and joint participation in taking action for future needs, 3) adapting in updating and adjusting learning according to the response needed 4) being fair, impartial in making decisions and open to challenges and feedback received. The breakthroughs made in this study to improve the quality of education are by mapping competencies by bringing similar learning areas closer together and evaluating them, selecting learning strategies that are innovative and creative in using media effectively, and utilizing information technology.…”
Section: Resultssupporting
confidence: 93%
“…Innovative leadership in education can be realized in managing and making decisions for the evaluation phase, starting at the planning, management, indicator development stages into a core program of innovative leadership in learning by paying attention to the adaptation of responsive and applicable information technology for implementation (Syafaruddin, Asrul, Mesiono, 2019). This is in line with the research of Nugroho et al, (2021) which says that innovative leadership is suitable in dealing with crises because of the advantages it has, such as 1) being able to anticipate needs, modes of interest and choice in the future, 2) being active in building knowledge and joint participation in taking action for future needs, 3) adapting in updating and adjusting learning according to the response needed 4) being fair, impartial in making decisions and open to challenges and feedback received. The breakthroughs made in this study to improve the quality of education are by mapping competencies by bringing similar learning areas closer together and evaluating them, selecting learning strategies that are innovative and creative in using media effectively, and utilizing information technology.…”
Section: Resultssupporting
confidence: 93%
“…Third, educational leaders need to develop empathy to encourage the work environment, increase productivity, and combine health interests on their personal and professional sides in accomplishing their duties. Fourth, educators need to develop heuristics for managing classrooms using technology in the new normal (Nugroho et al, 2021). Educators need to develop a set of heuristics for managing classrooms using technology in the new normal (Nugroho et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, educators need to develop heuristics for managing classrooms using technology in the new normal (Nugroho et al, 2021). Educators need to develop a set of heuristics for managing classrooms using technology in the new normal (Nugroho et al, 2021). Educators need to develop a set of heuristics for managing classrooms using technology in the new normal (Nugroho et al, 2021) Studies by Francisco & Nuqui (2020) in the Philippines found that in the Covid-19 era, education leaders need to have some new leadership skills.…”
Section: Discussionmentioning
confidence: 99%
“…Satuan tugas yang dibentuk dan dikendalikan oleh Kepala Sekolah SMA Al Hikmah Malang ini juga bertugas menangkal informasi-informasi yang tidak benar (hoax) dengan tujuan agar informasi yang diterima komponen sekolah termasuk masyarakat sekitar sekolah merupakan informasi yang benar dan memiliki derajad validitas yang tinggi. Hal ini sejalan dengan penelitian yang dilakukan oleh Sutama (2021), Suheny et al (2020) dan Nugroho et al (2021) yang menyatakan bahwa kepemimpinan adaptif sangat relevan dalam menghadapi krisis, karena dalam kepemimpinan adaptif melibatkan empat aspek yang penting yaitu (1) Antisipasi kebutuhan, tren, dan pilihan masa depan (2) Artikulasi, kebutuhan di masa mendatang untuk membangun pemahaman bersama dan dukungan untuk melaksanakan aksi. (3) Adaptasi mendorong pembelajaran berkelanjutan dan penyesuaian terhadap respon yang diperlukan (4) Akuntabilitas mencakup transparansi dalam proses pengambilan keputusan dan keterbukaan terhadap tantangan dan umpan balik.…”
Section: Hasil Dan Pembahasan Penelitianunclassified